2004
DOI: 10.1063/1.1711594
|View full text |Cite
|
Sign up to set email alerts
|

Cubatic liquid-crystalline behavior in a system of hard cuboids

Abstract: The lyotropic phase behavior of cuboidal particles was investigated via Monte Carlo simulations. Hard cubes were approximated by suitably shaped clusters of hard spheres. Changes in concentration and structure of the system were monitored as a function of osmotic pressure P* (imposed in an isobaric ensemble). As expected, an isotropic phase prevailed at low concentrations (low P*) and a crystalline phase formed at high concentrations (high P*). A third distinct phase was also observed for an intermediate range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
61
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 17 publications
6
61
2
2
Order By: Relevance
“…In contrast to earlier conjectures [11][12][13] , we now find clear evidence of layering in the cubatic phase (also observed in [32]) which becomes visible in our redefined particle distribution functions (see details in SI). While the finite size of our system prevents us from ascertaining the range of such a positional order, the appreciable D values observed at these densities indicates that the system has liquid-like behaviour and there is sufficient translational disorder for layers to rearrange dynamically.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…In contrast to earlier conjectures [11][12][13] , we now find clear evidence of layering in the cubatic phase (also observed in [32]) which becomes visible in our redefined particle distribution functions (see details in SI). While the finite size of our system prevents us from ascertaining the range of such a positional order, the appreciable D values observed at these densities indicates that the system has liquid-like behaviour and there is sufficient translational disorder for layers to rearrange dynamically.…”
contrasting
confidence: 52%
“…These ordered assemblies have distinctive electronic, optical, and dynamical properties 4,5 and are highly desirable for fabrication of advanced electronic, photonic, and rheological devices 6,7 . Although numerous theoretical [8][9][10][11][12][13] and experimental 14,15 studies on mesophase behaviour of particles with anisotropic shapes have been reported, a roadmap marking out the most probable mesophases that could be formed by constituent particles with particular geometrical features is still incomplete. Exploring such relations will translate into a deeper understanding of the phase behaviour of colloidal systems with different particle shapes; e.g., Jiao et al 16 reported that unlike ellipsoids, convex superballs can be optimally packed in dense Bravais lattices because they are less symmetric but more isotropic than the former.…”
mentioning
confidence: 99%
“…In three dimensions (3D), differences in particle shapes give rise to a variety of liquid crystal phases, such as smectic 16 and discoidal phases 17 . Beyond classic liquid crystals 16 , new forms, such as the cubatic phase 9,24 , have been predicted but thus far not observed.…”
mentioning
confidence: 99%
“…47,54 An alternative approach to modelling a polyhedron as a single object is by fusing repulsive spheres into a rigid body. Such models were used in early simulations of colloidal cubes, 55 although the slight corrugations of the cube surfaces introduced some noticeable artefacts. 54 Fused-sphere models with attractive spots have also provided the basis for seminal work on the self-assembly of virus capsids.…”
Section: Modelmentioning
confidence: 99%